Effect of Protein Intake on Strength, Body Composition and Endocrine Changes in Strength/Power Athletes - Kang Jie; Ratamess Nicholas A; Hoffman Jay R; Falvo Michael J; Faigenbaum Avery D (Taylor & Francis Group, 2006)
Abstract Comparison of protein intakes on strength, body composition and hormonal changes were examined in 23 experienced collegiate strength/power athletes participating in a 12-week resistance training program. Subjects were stratified into three groups depending upon their daily consumption of protein; below recommended levels (BL; 1.0 - 1.4 g·kg-1·day-1; n = 8), recommended levels (RL; 1.6 - 1.8 g·kg-1·day-1; n = 7) and above recommended levels (AL; > 2.0 g·kg-1·day-1; n = 8). Subjects were assessed for strength [one-repetition maximum (1-RM) bench press and squat] and body composition. Resting blood samples were analyzed for total testosterone, cortisol, growth hormone, and insulin-like growth factor. No differences were seen in energy intake (3,171 ± 577 kcal) between the groups, and the energy intake for all groups were also below the recommended levels for strength/power athletes. No significant changes were seen in body mass, lean body mass or fat mass in any group. Significant improvements in 1-RM bench press and 1-RM squat were seen in all three groups, however no differences between the groups were observed. Subjects in AL experienced a 22% and 42% greater change in Δ 1-RM squat and Δ 1-RM bench press than subjects in RL, however these differences were not significant. No significant changes were seen in any of the resting hormonal concentrations. The results of this study do not provide support for protein intakes greater than recommended levels in collegiate strength/power athletes for body composition improvements, or alterations in resting hormonal concentrations.